Snakes and lizards (Reptilia: Squamata) of the Opak River area, province of Daerah Istimewa Yogyakarta, Indonesia - Yudha, Donan Satria (2016)
Reptiles that commonly found in or around riverbanks are turtles, lizards, snakes and crocodiles. Nowadays, turtles and crocodiles are rarely found or seen around the river which flow across human settlement especially in Java. The Opak River is one of the biggest river that flowing across Daerah Istimewa Yogyakarta (DIY) Province. The Opak River upstream is located on the southern slope of Mount Merapi and it estuary is located on the southern beach of DIY (Depok beach), Bantul Regency. The research aimed to acquire data about the diversity of snakes and lizards (Reptilia: Squamata) along the Opak River in the DIY. The data of squamates diversity were acquired using a combination of several methods, i.e., VES (Visual Encounter Survey), riverbank cruising and transect. Sampling area generally divided into four locations, i.e., upstream, midstream, downstream, and estuary. Species diversity of squamates in the Opak River is consisted of 11 species of lacertilians (lizards) and 16 species of serpents (snakes). The Opak River is a decent habitat for some lizards and snakes.